2014
DOI: 10.1016/j.ijgo.2014.07.038
|View full text |Cite|
|
Sign up to set email alerts
|

Proportion of cervical excision for cervical intraepithelial neoplasia as a predictor of pregnancy outcomes

Abstract: The pretreatment cervical dimensions and the proportions of the volume/length excised vary substantially, and the latter correlates with the pregnancy duration. Assessment of the proportion excised might help to stratify women at risk who need intensive surveillance when pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 26 publications
5
64
0
2
Order By: Relevance
“…4,[8][9][10] However, in recent years, some studies have not been able to confirm the association between excisional treatment and increasing risk for preterm delivery. 4,[8][9][10] However, in recent years, some studies have not been able to confirm the association between excisional treatment and increasing risk for preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[8][9][10] However, in recent years, some studies have not been able to confirm the association between excisional treatment and increasing risk for preterm delivery. 4,[8][9][10] However, in recent years, some studies have not been able to confirm the association between excisional treatment and increasing risk for preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of cervical cancer screening 1,2 and subsequent excisional treatment of cervical intraepithelial neoplasia (CIN) have lowered the incidence of cervical cancer significantly in developed countries over the past 50 years. 3 Excisional treatment for cervical dysplasia has in several studies been found to be associated with an increased risk of preterm delivery 4,5 defined by the World Health Organization as birth before 37 weeks of gestation. Preterm delivery is the main cause of neonatal mortality as well as short-and long-term morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the human cervix to prevent bacteria ascending from the vagina to the uterine cavity depends on several factors, including a mucus plug that provides a negatively-charged platform for interaction with cationic antimicrobial peptides (AMPs) including the Human β-defensins (HBDs) 14,15 . It is not known why certain women develop ascending infection; women who have had previous cervical excisional treatment are associated with an increased risk of preterm birth 16 , but it is likely that an endogenous compromise in cervical mucosal immunity plays a key role in these cases 17 . In support of this, recent evidence has shown an association between PTB and low mid-trimester cervico-vaginal levels of human β-defensin 2 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that the pre-treatment cervix length and dimensions vary amongst women, it is biologically plausible that the proportion (percentage) of the cervix excised may correlate more accurately to the chances of adverse sequelae than the absolute dimensions, and that there may be a cut-off for the proportion of excision that signifies women at risk131415.…”
mentioning
confidence: 99%